Purification of Recombinant Staphylococcus WL1 Lipase Expressed in Escherichia coli BL21 (DE3) - ERIKA RAHAYU ( NIM : 10510025) ; Pembimbing Zeily Nurachman, D.Sc., ANISAH
Lipase is a hydrolytic enzyme that has been widely used in industry. In a previous study, gene encoding lipase of Staphylococcus WL1 (lipFWS) has been sequenced, cloned, and expressed in Escherichia coli BL21 (DE3). This study aims to purify the recombinant LipFWS with gel filtration column using diatom biosilica matrix. The methods included production of lipase, enzyme activity assay, and purification of protein by ammonium sulphate fractionation and gel filtration column. The results of this study showed that maximum recombinant LipFWS expressed in host cells E. coli BL21 (DE3) was induced by 0.5 mM IPTG for 4 h. SDS-PAGE of crude extract showed a protein band of approximately 49.7 kDa indicating that the recombinant LipFWS was successfully expressed intracellularly. The activity of the crude extract was 5.27 ± 1.82 U with a specific activity of 0.13 ± 0.03 U/mg. The salt fraction of enzyme had an activity of 0.88 ± 0.34 U with a specific activity of 0.05 ± 0.02 U/mg. Purification of LipFWS with gel filtration column using biosilica obtained from diatoms Navicula sp. and Nitzschia closterium showed fractions containing recombinant LipFWS. SDS-PAGE analysis of the fractions showed that a protein band with molecular weight approximately 49.7 kDa of fraction 10 from the biosilica N. closterium column was identified as recombinant LipFWS.